Systematic Literature Review : Analisis Penerapan Pendekatan Contextual Teaching And Learning Terhadap Kemampuan Komunikasi Matematis Siswa - Khaeriyah, Annisa Nur; Dani Firmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to analyze the application of the Contextual Teachingand Learning approach on mathematical communication skills. The researchmethod used is Systematic Literature Review (SLR), meaning that this study is theresult of a systematic review of literature on related topics. Relevant articles weresearched for those published between 2019 and 2024 that examined the ContextualTeaching and Learning (CTL) approach, mathematical communication, andmathematics learning. The literature review was based on online articles fromGoogle Scholar Scholar. Based on the research findings, there is a positive impactof the application of the Contextual Teaching and Learning (CTL) approach onmathematical communication skills because this student-centered learningencourages active engagement, connects the material to real-world contexts, andenhances self-confidence, motivation, and learning independence.